Estimation of cost synergies from mergers without cost data: Application to US radio - Przemysław Jeziorski (The Johns Hopkins University, Department of Economics, 2010)
This paper develops a new way to estimate cost synergies from mergers without using actual data on cost. The estimator uses a structural model in which companies play a dynamic game with endogenous mergers and product repositioning decisions. Such a formulation has several benefits over the widespread static merger analysis. In particular, it corrects for sample selection of more profitable mergers and captures follow-up mergers and post-merger product repositioning. The framework is applied to estimate cost efficiencies after the deregulation of U.S. radio in 1996. The procedure uses the data on radio station characteristics and numerous acquisitions, without explicit need for cost data. It turns out that between 1996 and 2006 additional ownership concentration generated 2.5b per-year cost savings, which is about 10% of total industry revenue.
Keywords: 330